Ethic and moral by the pampeanos veterinarians. Their premise, ethic code and discipline (Veterinary Science, 2017)
Exploratory qualitative and quantitative polls were done by a 131 veterinarian at Maraco Department of La Pampa, asking about how should be an ethic professional. In order to obtain reliable results, the answers were tabulated into five possible categories: general basics characteristics, clients, colleague, yourself and advertisement. Additionally, the practitioners were classified in enrolled or not, to the veterinary state union, the degree of knowledge of the code and labour condition. The results expressed significant differences among the way they think in relation to the proposed statements. In conclusion, for those how works in the private activities ethic is if you respect your colleagues. Finally, the results were discussing with qualified persons, who set out the responsibility of the veterinary state union and the Faculty of Veterinary Sciences, for not been on the agenda of either junior professional or vet student.
Keywords: ethics; ethic code; social responsibility; veterinarian